The impact of “4 + 7” volume-based drug procurement on the volume, expenditures, and daily costs of antihypertensive drugs in Shenzhen, China: an interrupted time series analysis - Ying Yang (BMC, 2021)
Abstract Background In 2019, Chinese government launched a nationwide volume-based drug procurement aiming at reducing drug prices and saving drug costs through economies of scale, which aroused widespread attention. The first round of the policy pilot was implemented in 4 municipalities and 7 sub-provincial cities, referred to as “4 + 7” policy. In the “4 + 7” policy, 7 antihypertensive drugs were included. This study was conducted to evaluate the impact of “4 + 7” policy on the use of policy-related antihypertensive drugs. Method This study applied single-group Interrupted Time Series (ITS) design. We used drug purchasing data from the Centralized Drug Procurement Survey in Shenzhen 2019, covering 24 months from January 2018 to December 2019. Antihypertensive drugs related to “4 + 7” policy were selected as study samples, including 7 drugs in the “4 + 7” List and 17 alternative drugs. Alternative drugs refer to antihypertensive drugs that have an alternative relationship with “4 + 7” List drugs in clinical use and have not yet been covered by the policy. “4 + 7” List drugs were then divided into bid-winning and bid-non-winning products according to the bidding results. Purchase volume, expenditures, and daily costs were selected as outcome variables, and were measured using Defined Daily Doses (DDDs), Chinese Yuan (CNY), and Defined Daily Drug cost (DDDc). Results After “4 + 7” policy intervention, the procurement volume of bid-winning antihypertensive drugs significantly increased (3.12 million DDD, 95 % CI = 2.14 to 4.10, p < 0.001), while the volume of non-winning drugs decreased (-2.33 million DDD, 95 % CI= -2.83 to -1.82, p < 0.01). The use proportion of bid-winning antihypertensive drugs increased from 12.31 to 87.74 % after policy intervention. The overall costs of the seven “4 + 7” List antihypertensive drugs significantly declined (-5.96 million CNY, 95 % CI= -7.87 to -4.04, p < 0.001) after policy intervention, with an absolute reduction of 36.37 million CNY compared with the pre-“4 + 7” period. The DDDc of bid-winning antihypertensive drugs significantly decreased (-1.30 CNY, 95 % CI= -1.43 to -1.18, p < 0.001), while the DDDc of non-winning (0.28 CNY, 95 % CI = 0.11 to 0.46, p < 0.01) and alternative (0.14 CNY, 95 % CI = 0.03 to 0.25, p < 0.05) antihypertensive drugs increased markedly. Conclusions The implementation of “4 + 7” policy promoted the drug use hypertensive patients gradually concentrated on the quality-guaranteed bid-winning drugs, which might be conducive to improve the overall quality level of drug use of Chinese hypertensive patients. Besides, a preliminary positive policy effect of price cut and cost-saving was observed in the antihypertensive drug category. In the future, price monitoring and drug use management regarding policy-related drugs should also be strengthened.